2001
DOI: 10.1046/j.1439-037x.2001.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tillage and Fertilization on Some Selected Physical Properties of Soil (0–30 cm Depth) and on the Root Growth Dynamic of Winter Barley (Hordeum vulgare cv. Niki)

Abstract: The root mass of winter barley (Hordeum vulgare cv. Niki) at growth stages 5, 9 and 16 of the Feekes scale increased from 100 % (0.272 mg cm–3 soil) to 132 % and 139 %, respectively. Root mass was always greater in no‐tillage (NT) plots than in ploughed‐tillage (CT) plots and was also greater where manure was applied in comparison to plots without manure. The root density at growth stages 5, 9 and 16 over all treatments was 0.197, 0.224 and 0.238 cm cm–3 soil, respectively. At growth stage 5, the root density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…The incorporation of organic manure into soil can bring beneficial effects on crop root growth by improving physical and chemical environments of rhizosphere (Sidiras et al 2002). A decrease in soil organic matter content can cause a decrease of root growth (Önemli 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of organic manure into soil can bring beneficial effects on crop root growth by improving physical and chemical environments of rhizosphere (Sidiras et al 2002). A decrease in soil organic matter content can cause a decrease of root growth (Önemli 2004).…”
Section: Resultsmentioning
confidence: 99%
“…However, tillage did not have a direct effect on the average MD, despite changes in the soil environment under NT. Pearson et al (1991) also reported that tillage had no effect on the diameter of winter wheat roots at anthesis in contrast to barley roots (Sidiras et al, 2001; Braim et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The root diameter may be indicative of the effects of soil strength on root growth and affects the utilization of nutrients in the soil. Sidiras et al (2001) reported thicker barley ( Hordeum vulgare L.) roots under CT than under NT, in contrast to Braim et al (1992), while Pearson et al (1991) found no effect of tillage on the diameter of wheat roots.…”
mentioning
confidence: 94%
“…Sidiras et al (2000) studied the effect of tillage on seedling emergence of barley (Hordeum vulgare L.) and found that seedling emergence was better in NT plots than in rotary hoed (minimum tillage) and ploughed (conventional tillage) treatments. In another experiment, Sidiras et al (2001) studied the effect of tillage on root growth dynamics of barley and found that root mass and root density were always greater in NT plots than in ploughed-tillage (CT) plots, whereas the diameter of barley roots was bigger in CT plots than in NT plots. In addition, Dhima et al (2006) studied the effect of three tillage systems (minimum, reduced, and conventional tillage) on growth and yield components of two six-row barley cultivars in presence or absence of sterile oat (Avena sterilis L.).…”
Section: Conservation Tillage In Greecementioning
confidence: 99%